The Export-Productivity Link in Brazilian Manufacturing Firms - Cirera, X.; Lederman, D.; Máñez, J.A.; Rochina, M.E.; Sanchis, J.A. (World Bank, Washington, DC, 2015)
This paper explores the link between exports and total factor productivity in Brazilian manufacturing firms over the period 2000–08. The Brazilian experience is instructive, as it is a case of an economy that expanded aggregate exports significantly, but with stagnant aggregate growth in total factor productivity. The paper first estimates firm-level total factor productivity under alternative assumptions (exogenous and endogenous law of motion for productivity) following a GMM procedure. In turn, the analysis uses stochastic dominance techniques to assess whether the ex ante most productive firms are those that start exporting (self-selection hypothesis). Finally, the paper tests whether exporting boosts firms’ total factor productivity growth (learning-by-exporting hypothesis) using matching techniques to control for the possibility that selection into exports may not be a random process. The results confirm the self-selection hypothesis and show that starting to export yields additional growth in total factor productivity that emerges since the firm’s first year of exporting but lasts only one year. Further, this extra total factor productivity growth is much higher under the assumption of an endogenous law of motion for productivity, which reinforces the importance of accounting for firm export status to study the evolution of productivity.